Evaluation of the Shear Bond Strength and Adhesive Remnant Index in Debonding of Stainless Steel Brackets Assisted with Nd:YAG Laser Irradiation - Maryam Nasiri; Seyed Amir Hossein Mirhashemi; Ardavan Etemadi; Mohammad Javad Kharrazi fard; Elahe Soltanmohamadi Borujeni; Maryam Javaheri Mahd; Pegah Khazaei; Mohammad Sadegh Ahmad Akhoundi (Tehran University of Medical Sciences, 2019)
Objectives: The purpose was to compare shear bond strength (SBS), pulp temperature, and adhesive remnant index (ARI) in debonding of stainless steel brackets from enamel surface using neodymium-doped yttrium aluminum garnet (Nd:YAG) laser versus the conventional debonding method. Materials and Methods: Forty-eight extracted premolars were bonded to stainless steel brackets. The samples were divided into three experimental groups and one control group. In the first three groups, Nd:YAG laser was used for debonding with the power of 1, 1.5, and 2 W, respectively, for 10 seconds. The SBS and ARI of the samples were assessed. Pulp temperature was recorded before and after irradiation. Two samples from each group were used for determining enamel morphology after debonding using scanning electron microscopy (SEM). Results: The mean SBS in the groups was 33.05, 28.69, 24.37, and 31.53 MPa, respectively, with no statistically significant differences (P=0.205). Significant differences in post-irradiation temperature were noted among the lased groups (P=0.000). Debonding mainly occurred at the adhesive-enamel interface in the 1-W laser and control groups and at the bracket-adhesive interface in the 1.5-W and 2-W laser groups. Enamel structure was amorphous and irregular following laser irradiation. Conclusions: Based on the results of this study, the use of Nd:YAG laser could not significantly affect the SBS. Therefore, this laser would not be suitable for debonding of metal brackets. The use of a 2-W laser could significantly raise the pulpal temperature. Nd:YAG laser renders a more heterogeneous enamel morphology compared to conventional debonding methods.